An Analysis on Understanding Child Abuse and Maltreatment/Neglect: Addressing Child Abuse and Maltreatment in Developing Countries (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Child maltreatment is a global problem but is moredifficult to assess and manage in developing countries such as India whereone-fifth of the world’s total child population resides. Certain forms ofmaltreatment such as feticide, infanticide, abandonment, child labour, street-begging,corporal punishment and battered babies are particularly prevalent in India.Most physicians still need to be sensitized in order to suspect child abuse onthe basis of unexplained trauma, multiple fractures, parental conflict andother corroborative evidence. A culture of non-violence towards children needs to bebuilt into communities in order to provide an environment conducive to theoverall development of the child. Rehabilitation of abused children and theirfamilies requires a multi-disciplinary service including paediatricians, childpsychologists and social workers, and the training of police forces in how totackle the problem.